Pengaruh Kualitas Produk dan Desain Produk terhadap Keputusan Pembelian Motor Merek Honda Beat: (Study Kasus pada Konsumen Dealer AHASS Lahat) - Fytaloka, Vemi; Mujari; Pratiwi, Dini (Business Perspective Journal, 2025)
This research aims to examine the influence of selling price and distribution channels on the sales This research aims to determine the influence of product quality and product design on purchasing decisions for Honda Beat brand motorbikes (case study of Ahass Lahat dealer customers). The number of samples in this research was 62 customers who bought Honda brand motorbikes at Ahhas dealers. The approach taken in this research was an associative approach and the type of data used was quantitative data using multiple regression analysis techniques which were processed using the SPSS version 24 application and produces the regression equation Y = 10,203 +0,284X_1 +〖0,330X〗_2 . The results of this study indicate that there is a significant influence between product quality and product design on the decision to purchase a Honda brand motorbike (case study on Ahass Lahat dealer customers), the f test shows that product quality and product design influence the decision to purchase a Honda brand motorbike (case study on ahass Lahat dealer customers). Keywords: product quality, product design, purchase decision